3D template-based Fermi-LAT constraints on the diffuse supernova axion-like particle background - Calore, Francesca; Carenza, Pierluca; Eckner, Christopher; Fischer, Tobias; Giannotti, Maurizio; Jaeckel, Joerg; Kotake, Kei; Kuroda, Takami; Mirizzi, Alessandro; Sivo, Francesco (Physical review, 2022)
Axion-like particles (ALPs) may be abundantly produced in core-collapse (CC) supernovae (SNe); hence, the cumulative signal from all past supernova (SN) events can create a diffuse flux peaked at energies of about 25 MeV. We improve upon the modeling of the ALPs flux by including a set of CC SN models with different progenitor masses, as well as the effects of failed CC SNe, which yield the formation of black holes instead of explosions. Relying on the coupling strength of ALPs to photons and the related Primakoff process, the diffuse SN ALP flux is converted into gamma rays while traversing the magnetic field of the Milky Way. The spatial morphology of this signal is expected to follow the shape of the Galactic magnetic field lines. We make use of this via a template-based analysis that utilizes 12 years of Fermi-LAT data in the energy range from 50 MeV to 500 GeV. In our benchmark case of the realization of astrophysical and cosmological parameters, we find an upper limit of gaγ≲3.76×10−11 GeV−1 at a 95% confidence level for ma≪10−11 eV, while we find that systematic deviations from this benchmark scenario induce an uncertainty as large as about a factor of two. Our result slightly improves the CAST bound, while still being a factor of six (baseline scenario) weaker than the SN1987A gamma-ray burst limit.
Gesehen am 30.05.2022